2021
DOI: 10.1002/agj2.20745
|View full text |Cite
|
Sign up to set email alerts
|

Auxin increased adventitious root development in the medicinal plant Andrographis paniculata (Burm. f.) Wall. ex Nees

Abstract: Andrographis paniculata (Burm. f.) Wall. ex Nees is an economically high‐demand medicinal plant for its traditional uses and overwhelming pharmacological properties. However, the current agricultural production of A. paniculata is insufficient to meet its pharmacological demand. Developing a rapid and efficient propagation technique is crucial to meet its increasing demand. This study assessed the ability of the auxins indole‐3‐butyric acid (IBA) and indole‐3‐acetic acid (IAA) to simulate adventitious root dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Nature contains plenty of sources for the first line of treatment and prominent compounds to treat many severe diseases [ 142 , 143 ]. An estimation reported that approximately 75–80% of the world’s population uses traditional medical systems as their first therapy option due to lack of access to treatment facilities as well as worries about synthetic medicine safety and efficacy [ 144 , 145 ]. On the other hand, natural products have grown in importance as sources of polypharmacological treatments for infectious diseases, malignancies, and neurological disorders [ 146 , 147 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Nature contains plenty of sources for the first line of treatment and prominent compounds to treat many severe diseases [ 142 , 143 ]. An estimation reported that approximately 75–80% of the world’s population uses traditional medical systems as their first therapy option due to lack of access to treatment facilities as well as worries about synthetic medicine safety and efficacy [ 144 , 145 ]. On the other hand, natural products have grown in importance as sources of polypharmacological treatments for infectious diseases, malignancies, and neurological disorders [ 146 , 147 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…A placebocontrolled double-blind study of Kan Jang TM showed better efficacy of A. paniculata extracts than a placebo for reducing clinical symptoms among 59 common cold patients [4]. This evidence indicates that A. paniculata has a high market value, either in the form of its parts or standard compounds (e.g., 5 USD kg −1 and 100,000 USD kg −1 for good-quality dried leaves and andrographolide, respectively) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The biological activities of A. paniculata could be associated with the presence of approximately 142 secondary metabolites in this plant's tissues, including entalabdane diterpenoids, flavonoids, quinic acid derivatives, xanthones, rare noriridoids, steroids, and other compounds [5,6]. Most of them are extracted from the aerial parts, leaves, and whole parts of the plant, while some are obtained from the roots (Figure 1).…”
Section: Introductionmentioning
confidence: 99%